DNA Sequencing by Hybridization and Shotgun Sequencing Technique (International Journal of Advanced Research in Computer Science, 2017)
DNA sequencing includes several methods and technologies that are used for determining the order of the nucleotide bases adenine, guanine, cytosine, and thymine in a molecule of DNA. Knowledge of DNA sequences has become indispensable for basic biological research, other research branches utilizing DNA sequencing, and in numerous applied fields such as diagnostic, biotechnology, forensic biology and biological systematic. The advent of DNA sequencing has significantly accelerated biological research and discovery. The rapid speed of sequencing attained with modern DNA sequencing technology has been instrumental in the sequencing of the human genome, in the Human Genome Project. Related projects, often by scientific collaboration across continents, have generated the complete DNA sequences of many animal, plant, and microbial genomes. The first DNA sequences were obtained in the early 1970s by academic researchers using laborious methods based on two-dimensional chromatography. Following the development of dye-based sequencing methods with automated analysis DNA sequencing has become easier and orders of magnitude faster. Common challenges of DNA sequencing include poor quality in the first 15–40 bases of the sequence and deteriorating quality of sequencing traces after 700–900 bases. So we have a challenge for a good quality after sequencing [1] [7] [10].Keywords: DNA, SHOTGUN, SBH, GA.